Graphene nanoplatelets promoted CoO-based catalyst for low temperature CO2 methanation reaction - Zhong, Liping; Pham, Thi Ha My; Ko, Youngdon; Züttel, Andreas (Frontiers in Chemical Engineering, 2023)
Methanation of CO2 is an important reaction for Power-to-Gas system and reducing CO2 emission. Compared to cobalt supported on gamma-Al2O3 oxide, cobalt supported on graphene nanoplatelets (GNPs) shows significantly better performance for CO2 methanation process. Cobalt supported on GNPs has enhanced the CO2 conversion at low temperatures below 250oC from 5% of cobalt supported on Al2O3 to about 15%. In situ thermogravimetric analysis (TGA) has demonstrated that the Co/GNPs catalyst is stable even up to 400oC. However, the maximum catalyst mass specific CH4 yield is obtained at a cobalt loading of 5 wt% on GNPs, whereas high cobalt loading on GNPs deactivates the reactivity of the Co/GNPs catalyst. Transmission electron microscopy (TEM) results demonstrate that 5wt% Co/GNPs sample has the smallest and most dispersed cobalt nanoparticles. Excessive loading of cobalt tends to form isolated large cobalt nanoparticles. Xray photoelectron spectroscopy (XPS) and Raman Spectra analysis realized that more CoO phases are maintained on the surface of 5wt%Co/GNP, indicating that the metal-support interaction between Co and GNPs has more of an impact on cobalt's redox capacity than does particle size, which ultimately affects cobalt's active phase during the CO2 reduction process. Furthermore, Raman spectra demonstrate that the loading of cobalt leads to the increase of graphene defects. Nevertheless, increasing cobalt loading to GNPs results less interfaces between cobalt and GNPs due to the agglomeration of cobalt nanoparticles.